2012
DOI: 10.1021/ja302959e
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Amyloid Fibrils: An Excellent Platform for Controlled Synthesis of Ultrathin Superlong Platinum Nanowires with High Electrocatalytic Activity

Abstract: Highly uniform single-crystal ultrathin Pt nanowires (UTPtNWs) with a diameter of ~1.8 nm and a superhigh aspect ratio of >10(4) were fabricated using insulin amyloid fibrils (INSAFs) as sacrificial templates. The use of INSAFs to build the UTPtNWs allowed for the preferential exposure of low-energy crystal facets that would be highly advantageous for the methanol oxidation reaction. The UTPtNWs displayed a large electrochemical active surface area of 71.34 m(2)/g, which is much higher than that of a commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 30 publications
1
114
0
1
Order By: Relevance
“…[17][18][19][20][21][22][23] It is, however, aiming at reducing the usage of the precious Pt metal and hence the cost of FCs, the development of non-Pt electrocatalysts has thus generated a great deal of interest. 9 It has shown that the Pd is a promising electrocatalyst because of much cheaper than Pt and highly electroactive to the small organic molecules (i.e.…”
Section: 2mentioning
confidence: 99%
“…[17][18][19][20][21][22][23] It is, however, aiming at reducing the usage of the precious Pt metal and hence the cost of FCs, the development of non-Pt electrocatalysts has thus generated a great deal of interest. 9 It has shown that the Pd is a promising electrocatalyst because of much cheaper than Pt and highly electroactive to the small organic molecules (i.e.…”
Section: 2mentioning
confidence: 99%
“…Unlike previous reports involving utilization of Pt electrodes 8,[19][20][21][22] , the selection of single-layered 2D Ni(OH) 2 (SL-Ni(OH) 2 ) nanosheets as the substrates is based on cost considerations 28,29 , as SL-Ni(OH) 2 sheets might be cheaply acquired via exfoliation of lamellar a-Ni(OH) 2 (refs 30-33). Furthermore, compared with commonly used zero-dimensional (0D) Pt nanoparticles (NPs), 1D ultrathin Pt NWs of high aspect ratios, few lattice boundaries and smooth crystal planes offer the opportunity for improvement of the catalytic activity [34][35][36][37][38][39][40][41][42][43][44] . Meanwhile, a large contact area between Pt NWs and the Ni(OH) 2 substrates can effectively alleviate possible migration and aggregation of Pt NWs and thus benefit enhancement of the catalytic stability 40 .…”
mentioning
confidence: 99%
“…16 By incubating INSAFs in metal salt solution for several hours, the selected amide sites on INSAFs can recognize and interact with metal ions. 15 After reduction, Pt-Pd nanoparticles grew in situ sites and formed 1D nanoparticle chains structure. The low-magniÂŻcation TEM image [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 However, the direct synthesis of 1D Pt-M nanocrystals by using INSAFs has not been achieved. Here, Pt-Pd nanoparticles with an uniform particle size of 2.5 nm were synthesized along the insulinÂŻbrils, and thus formed a 1D chain structure with length up to several micrometers.…”
Section: Introductionmentioning
confidence: 99%